Problems of Prevention and Treatment of Diaper Dermatitis in Children within the Current Concepts of the Disease Pathogenesis - Nikolay N. Murashkin; Larisa S. Kruglova; Alexander I. Materikin; Eduard T. Ambarchian; Roman V. Epishev (Union of pediatricians of Russia, 2018)
Diaper dermatitis is a disease belonging to the group of contact dermatitis. Clinical manifestations include skin inflammation in the area of contact with the diaper due to barrier epidermal dysfunction. The paper analyses the pathogenesis of the disease and presents data on a local clinical study on the safety and efficacy of the medication with a regenerative potential.